A cross-national data collaboration of domestic violence specialist courts: a research note - Holder, Robyn L. (International journal of comparative and applied criminal justice, 2020)
Specialised domestic violence (DV) courts exist in a number of common law countries. While site-specific evaluations show promise, there remains much dissimilarity to the processes and components of these courts that raise questions about cross-national comparison. This article discusses a project to reduce data variation by applying a standardised data grid in court sites in three different countries. Part of a larger research programme of the Canadian Observatory on Justice Responses to Intimate Partner Violence, the pilot shows that, with site-specific adaptions, a standardised grid can reduce variation and is feasible as a data-collection instrument. However, the pilot also reveals how the shared objectives of specialised DV courts across countries are undermined by the absence of core data especially that related to victims. Further, standardised cross-national court data collection can unhelpfully minimise differences in local legal and social cultures that are important to justice system priority-setting.